Kazim Ali’s poetry: Sky Ward negotiating postmodern identity - Ali, Nehal; Abbas, Mohsen (Research Journal in Advanced Humanities, 2026)
The postmodern belief is more mental structures in response to rapid changes in thinking, creativity, awareness, conduct, and authority. Kazim Ali is a contemporary poet inspired by technology. Sky Ward, his poetry book, examines how technology affects relationships and creativity. In this research, postmodernist features in Kazim Ali's poetry are analyzed, along with how he metaphorically reflects his native North America and his ancestors' homelands in his writing. This study takes a multifaceted look at the poetics of diaspora, with a particular focus on the diasporic identities of those who are of the second generation of immigrant families. This study also investigates the ways in which second-generation immigrants construct metaphorical homelands via the use of familial narrative and early recollections of their ancestors. In addition to this, it investigates the ways in which loss expresses itself for authors who live in liminality, as well as the ways in which contradicting experiences or plurality are depicted by gaps in both the formal structure of a poem and its intellectual landscape.